2014
DOI: 10.5301/jbm.5000058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of microRNA-221/222 Expression in Cancers: Evidence from 1,204 Subjects

Abstract: The meta-analysis demonstrates that the elevated expression of miR-221 and miR-222 is associated with poor OS in patients with cancer. The miR-221/222 cluster might be used as a potential therapeutic strategy in clinical practice. More work is required to fully elucidate the role of the miR-221/222 family in human tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(197 reference statements)
2
7
0
Order By: Relevance
“…Recently published studies show that miR-221 is an oncogenic microRNA involved in several malignancies (30,31). We found higher miR-221 expression in tumor samples in comparison to adjacent noncancerous tissue.…”
Section: Patients Below Patients Abovesupporting
confidence: 50%
“…Recently published studies show that miR-221 is an oncogenic microRNA involved in several malignancies (30,31). We found higher miR-221 expression in tumor samples in comparison to adjacent noncancerous tissue.…”
Section: Patients Below Patients Abovesupporting
confidence: 50%
“…In the first meta-analysis of miR-222 related to the outcomes of various cancers, Wang et al retrieved 4 studies and found that high miR-222 expression is negatively correlated with the clinical outcome, with a pooled HR of 2.15 [49]. Nevertheless, the relatively small study size limited the power of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis is capable to obtain relatively accurate estimation by integrating all available evidence to explore authentic and comprehensive results. 11 The only meta-analysis regarding the prognostic value of miRNA-221/222 cluster in cancers was published in 2013 by Wang et al 12 Thus, we carried out an updated meta-analysis with larger sample size, more cancer types, more ethnicities, and different analysis models to verify the previous conclusions and especially uncover some novel findings, which may contribute to the exploration of new promising biomarkers for assessing the therapeutic efficacy and prognostic value of different types of cancers.…”
Section: Introductionmentioning
confidence: 99%